The Effect Of Behavioral Finance, Investment Experience, And Risk Tolerance On Financial Allocation In Bond Instruments: - - Kennale Justin Wang; I Gede Adiputra (Cita konsultindo, 2026)
In recent years, investment interest among the younger generation, particularly Generation Z, has increased significantly. This increase is inseparable from the development of financial technology and social media, which provide easy access to investment information and various digital financial services (Widjanarko, 2023). The availability of various financial instruments provides individuals with alternatives in allocating their funds. This condition indicates that financial decisions are no longer solely based on rational considerations, but are also influenced by psychological factors, individual experience, and risk preferences. This research is motivated by the increasing participation of Generation Z investors in the Indonesian capital market, particularly in bonds, which are influenced not only by rational factors but also by behavioral aspects, experience, and risk tolerance. Therefore, this study analyzes the influence of behavioral finance, investment experience, and risk tolerance on financial allocation in bond instruments. The results of this study indicate that behavioral finance has a positive and significant effect on financial allocation, investment experience does not have a significant effect on financial allocation, and risk tolerance does not have a significant effect on financial allocation.